2020
DOI: 10.3390/v13010049
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of SARS-CoV-2 and SARS-Like Coronavirus Diversity in Human, Bat and Pangolin Populations

Abstract: In 2019, a novel coronavirus, SARS-CoV-2/nCoV-19, emerged in Wuhan, China, and has been responsible for the current COVID-19 pandemic. The evolutionary origins of the virus remain elusive and understanding its complex mutational signatures could guide vaccine design and development. As part of the international “CoronaHack” in April 2020, we employed a collection of contemporary methodologies to compare the genomic sequences of coronaviruses isolated from human (SARS-CoV-2; n = 163), bat (bat-CoV; n = 215) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…Such computational studies compared the sequences of the six open reading frames (ORFs) of the isolates, in addition to the sequence of the 16 non-structural proteins and the four structural proteins (M, N, E, and S). Moreover, the studies compared their codon us age , misse nse m u t atio ns, a nd v arian t l eve l s. Furthermore, the studies compared the CpG dinucleotide contents and mutation patterns of SARS-CoV-2 clades and their related viruses (Dimonaco et al 2020;Matyášek and Kovařík 2020). The performed computational analysis supported other reports considering RaTG13 coronavirus isolated from Rhinolophus affinis (horseshoe bat) as the ancestor of SARS-CoV-2 virus.…”
Section: Computational Analysis Of Sars-cov-2 and Related Cladessupporting
confidence: 60%
See 1 more Smart Citation
“…Such computational studies compared the sequences of the six open reading frames (ORFs) of the isolates, in addition to the sequence of the 16 non-structural proteins and the four structural proteins (M, N, E, and S). Moreover, the studies compared their codon us age , misse nse m u t atio ns, a nd v arian t l eve l s. Furthermore, the studies compared the CpG dinucleotide contents and mutation patterns of SARS-CoV-2 clades and their related viruses (Dimonaco et al 2020;Matyášek and Kovařík 2020). The performed computational analysis supported other reports considering RaTG13 coronavirus isolated from Rhinolophus affinis (horseshoe bat) as the ancestor of SARS-CoV-2 virus.…”
Section: Computational Analysis Of Sars-cov-2 and Related Cladessupporting
confidence: 60%
“…Uniquely, both RaTG13 and SARS-CoV-2 clades exhibited CpG depletion in their genomes in contrast to other known coronaviruses (Matyášek and Kovařík 2020). Behind RaTG13 isolate, the pangolin-MP789 isolate ranked in the second position as closest relative to SARS-Co2 virus (Dimonaco et al 2020;Alexandrova et al 2020). Finally, members of order Chiroptera consist of more than 1400 different species of bats, not all of them can support SARS-CoV-2 replication (Boni et al 2020).…”
Section: Computational Analysis Of Sars-cov-2 and Related Cladesmentioning
confidence: 99%
“…Early phylogenetic studies on SARS-CoV-2 genomic sequences showed that it clustered closely with sequences originating from SARS-like viruses from bats within lineage B of the betacoronavirus genus. Lineage A groups are prototypical coronaviruses such as MHV and the human coronaviruses HCoV-HKU1 and HCoV-OC43 ( Figure 1 A,B) ([ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] tree.bio.ed.ac.uk/software/figtree/ accessed on 7 July 2021) (Software (ed.ac.uk accessed on 7 July 2021)), while the other highly pathogenic coronavirus, MERS-CoV, is found within lineage C, along with the related camel-derived MERS-CoV ([ 41 , 42 ] and references therein). The S protein amino acid sequences from four representative beta coronaviruses (HCoV-HKU1, MHV, SARS-CoV, and MERS-CoV) were aligned and the solved S protein structures were compared to determine their amino acid identity and the overall structural organization similarities among these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Further, for SARS-CoV-2, different results were reported, indicating from a main role of mutational pressure, to a strict selection pressure [33,[36][37][38]. In the case of human coronaviruses, including SARS-CoV, MERS-CoV and SARS-CoV-2, several CUB analyses were carried out [26,33,[43][44][45][46][47][48][49][35][36][37][38][39][40][41][42]. As a result, some general conclusions could be made: first, all of them possessed high AU content and low GC content, with the CpG dinucleotide markedly under-represented, and in the case of SARS-CoV-2, a preferred use of U-ending codons; codon usage bias and codon pair usage were found to be quite different from that of the human host, even when particular tissues such as lung and kidneys were analyzed [50]; high Effective Number of Codons (ENC) [51] values were found (although lower than those of other coronaviruses), suggesting a slight codon usage bias; in comparison to other coronaviruses, SARS-CoV, MERS-CoV, and SARS-CoV-2 presented the highest values of the Codon Adaptation Index (CAI) [52] calculated using human proteins as the reference set, suggesting that these viruses are more adapted to the human host than other coronaviruses that present milder clinical symptoms; a relatively high average CAI value was found for SARS-CoV-2 (approximately 0.7), however, its value was smaller than the average for human genes (approximately 0.8) [44].…”
Section: Introductionmentioning
confidence: 99%